Intracapsular tonsillectomy in the treatment of recurrent and chronic tonsillitis in adults: a protocol of a prospective, single-blinded, randomised study with a 5-year follow-up (the FINITE trial) - Piitulainen Jaakko Matias; Uusitalo Tapani; Sjöblom Henrik M; Ivaska Lotta E; Jegoroff Henri; Kauko Tommi; Kokki Hannu; Kytö Eero; Mansikka Iisa; Ylikoski Jenni; Jero Jussi (BMJ PUBLISHING GROUP, 2022)
INTRODUCTION
The standard surgical treatment for recurrent or chronic tonsillitis is extracapsular tonsillectomy. Recent studies show that intracapsular tonsillectomy has the potential to reduce the postoperative morbidity of patients undergoing tonsil surgery. The Finnish Intracapsular Tonsillectomy (FINITE) trial aims to provide level I evidence to support the hypothesis that the recovery time from tonsil surgery can be reduced with intracapsular tonsillectomy. Additionally, from this trial, major benefits in quality of life, reduction of postoperative complications, treatment costs and throat symptoms might be gained.
METHODS AND ANALYSIS
The FINITE trial is a prospective, randomised, controlled, patient-blinded, three-arm clinical trial. It is designed to compare three different surgical methods being extracapsular monopolar tonsillectomy versus intracapsular microdebrider tonsillectomy versus intracapsular coblation tonsillectomy in the treatment of adult patients (16-65 years) suffering from recurrent or chronic tonsillitis. The study started in September 2019, and patients will be enrolled until a maximum of 200 patients are randomised. Currently, we are in the middle of the study with 125 patients enrolled as of 28 February 2022 and data collection is scheduled to be completed totally by December 2027. The primary endpoint of the study will be the recovery time from surgery. Secondary endpoints will be the postoperative pain scores and the use of analgesics during the first 3 weeks of recovery, postoperative haemorrhage, quality of life, tonsillar remnants, need for revision surgery, throat symptoms, treatment costs and sick leave. A follow-up by a questionnaire at 1-21 days and at 1, 6, 24 and 60 months will be conducted with a follow-up visit at the 6-month time point.
ETHICS AND DISSEMINATION
Ethical approval was obtained from the Medical Ethics Committee of the Hospital District of Southwest Finland (reference number 29/1801/2019). Results will be made publicly available in peer-reviewed scientific journals.